Preclinical evaluation of three polyspecific antivenoms against the venom of Echis ocellatus: Neutralization of toxic activities and antivenomics - Calvete Chornet, Juan José (2016)
Snakebite envenoming has a heavy burden in the public health in sub-Saharan Africa. The viperid species Echis ocellatus (carpet viper or saw-scaled viper) is the medically most important snake in the savannahs of western sub-Saharan Africa. Several antivenoms are being distributed and used in this region for the treatment of envenomings by E. ocellatus, but the preclinical efficacy of some of these antivenoms has not been assessed. The present study evaluated the preclinical efficacy against E. ocellatus venom of three polyspecific antivenoms: (a) Snake Venom Antiserum (Pan Africa), manufactured by Premium Serums and Vaccines (India); (b) Snake Venom Antiserum (Africa), manufactured by VINS Bioproducts (India); and (c) Antivipmyn® Africa, manufactured by Instituto Bioclon (Mexico). Antivenomics analysis revealed the ability of the three antivenoms to immunocapture the majority of components of the venoms of E. ocellatus from Cameroon, Nigeria and Mali, although their maximal immunocapturing capability varied. Bioclon and Premium Serums antivenoms were effective in the neutralization of lethal, hemorrhagic and in vitro coagulant activities of the venom of E. ocellatus from Cameroon, albeit with different potencies. VINS antivenom neutralized hemorrhagic activity of this venom, but failed to neutralize lethality at the highest antivenom dose tested, and had a low neutralizing efficacy against in vitro coagulant effect.